2013
DOI: 10.1002/syn.21644
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine‐induced modulation of neural activities in the ventrolateral striatum of rats

Abstract: The dopaminergic system in the ventrolateral portion of the striatum (Svl), part of the basal ganglia, regulates orofacial movements; bilateral co-stimulation of both dopamine D1 -like and D2 -like receptors elicits repetitive jaw movements in rats. However, how the activities of Svl neurons are modulated by the activation of dopaminergic receptors remains unknown. We systematically injected apomorphine, a non-selective dopamine receptor agonist that induced jaw movements under urethane anesthesia, and perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Similarly, an acute block of the MFB by TTX also increases the firing rate (Prosperetti et al, 2013). Interestingly, while apomorphine likewise suppresses the firing rates of TANs (Fujita et al, 2013), D-Amphetamine, which increases the release of dopamine and inhibits its re-uptake, leads to an increased firing rate of TANs (Kish et al, 1999). In the non-human primate, no effect on spontaneous discharge rate of TANs by localized microinjections of either a D2 antagonist (sulpiride) or a D1 antagonist (SCH23390) (Watanabe and Kimura, 1998), or by unilateral dopamine depletion by MPTP infusion to the caudate-putamen complex (Aosaki et al, 1994a), was observed in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an acute block of the MFB by TTX also increases the firing rate (Prosperetti et al, 2013). Interestingly, while apomorphine likewise suppresses the firing rates of TANs (Fujita et al, 2013), D-Amphetamine, which increases the release of dopamine and inhibits its re-uptake, leads to an increased firing rate of TANs (Kish et al, 1999). In the non-human primate, no effect on spontaneous discharge rate of TANs by localized microinjections of either a D2 antagonist (sulpiride) or a D1 antagonist (SCH23390) (Watanabe and Kimura, 1998), or by unilateral dopamine depletion by MPTP infusion to the caudate-putamen complex (Aosaki et al, 1994a), was observed in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Male Sprague‐Dawley rats (Sankyo Laboratories) weighing 200.1 ± 4.5 g ( n = 11) were anesthetized as above. The surgical and recording procedures were as described previously (Fujita et al, ). A small craniotomy and resection of the dura mater was carefully performed to insert a recording electrode into the left side of the IC.…”
Section: Methodsmentioning
confidence: 99%
“…Unilaterally lesioned animals before transplantation (LES., green and black bars, n = 9, Supplementary Video 6) showed a strong preference for pellet retrieval ipsilateral to the lesion. Injection of the dopamine-receptor-agonist apomorphine, which signals through lesion-sensitized dopamine receptors on medium spiny neurons (MSNs) 22,23 and striatal interneurons 22 , resulted in an inversion of pellet retrieval behavior (green LES. bar + APO and Supplementary Video 7).…”
mentioning
confidence: 99%